2007
DOI: 10.1103/physrevb.76.174305
|View full text |Cite
|
Sign up to set email alerts
|

Single-polaron properties of the one-dimensional breathing-mode Hamiltonian

Abstract: We investigate numerically various properties of the one-dimensional (1D) breathing-mode polaron. We use an extension of a variational scheme to compute the energies and wave-functions of the two lowest-energy eigenstates for any momentum, as well as a scheme to compute directly the polaron's Green's function. We contrast these results with results for the 1D Holstein polaron. In particular, we find that the crossover from a large to a small polaron is significantly sharper. Unlike for the Holstein model, at m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
35
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 52 publications
1
35
1
Order By: Relevance
“…Recent neutron diffraction and electron microscopy experiments have, however, shown that the local structure is more subtle, with features that were irresolvable in the earlier X-ray diffraction data [28]. In fact, these new data on fully stuffed Ho SSI, Ho 2.67 Ti 1.33 O 6.67 , show that a separation of the Ho and Ti sites occurs due to the mismatch in the cation sizes, resulting in complex structural domains.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Recent neutron diffraction and electron microscopy experiments have, however, shown that the local structure is more subtle, with features that were irresolvable in the earlier X-ray diffraction data [28]. In fact, these new data on fully stuffed Ho SSI, Ho 2.67 Ti 1.33 O 6.67 , show that a separation of the Ho and Ti sites occurs due to the mismatch in the cation sizes, resulting in complex structural domains.…”
Section: Introductionmentioning
confidence: 88%
“…A possible explanation is that the dissimilarity in the entropy data arises from the differences in the structural domains of local pyrochlore order. Contrary to data for Ho SSI, X-ray diffraction data for Dy SSI do show peaks 9 corresponding to pyrochlore order for all values of x [27], and recent electron microscopy measurements, similar to those performed on Ho SSI [28], show that the pyrochlore domains in Dy SSI are an order of magnitude larger than those in the Ho SSI [36]. We hypothesize that the observed zero point entropy in Ho SSI may be associated with spins in the boundary regions between such domains, and the larger domains found in Dy SSI result in the observation of less zero point entropy due to the relatively smaller fraction of spins in such boundary regions.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations